Implementing Scalable Data Architecture for Financial Institutions - Bagam, Naveen (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
The finance sector generates vast volumes of complex data, which require scalable and robust architectures for efficient storage, processing, and analytics. Scalable data architecture is the basis that will make financial institutions competitive, compliant, and innovative in the modern fast-developing digital landscape. This paper addresses the principles, technologies, and methodologies necessary to implement scalable data architecture, keeping in mind high availability, security, and performance optimization as challenges. This paper is geared with real-world examples, technical frameworks, and performance metrics to provide actionable insights on scalability: both for legacy systems and new implementations.